Bitumen (Dampf und Aerosol bei der Heißverarbeitung) [MAK value documentation in German language, 2019]. Issue 3 (1st August 2019) - Nies, E.; Brüning, T.; Steinhausen, M.; Welge, P.; Werner, S.C.M.; Pallapies, D.; Bartsch, R.; Brinkmann, B.; Schriever‐Schwemmer, G.; Hartwig, A.
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the classification of bitumen [8052‐42‐4 ; 64741‐56‐6 ; 64742‐93‐4 ] in Carcinogen Category 2 considering all toxicological endpoints. New data allowed a separate assessment of the harmful properties of vapours and aerosols from high‐temperature processing of two bitumen groups. Straight‐Run and Air‐Rectified Bitumen For the derivation of a maximum concentration at the workplace (MAK value), a 2‐year inhalation study in rats exposed to vapours and aerosols from a mixture of straight‐run and air‐rectified bitumen is used. Due to an increased incidence of bronchioalveolar hyperplasia in the lungs and of inflammatory cells in the nasal epithelium, the study resulted in a NOAEC of 6 mg/m 3 . Taking into account the extrapolation from an animal study and the increased respiratory volume at the workplace compared with the exposure of the animals at rest, a MAK value of 1.5 mg/m 3 (sum of vapour and inhalable fraction) is derived for straight‐run and air‐rectified bitumen based on bitumen condensate standard. The MAK value is one‐third of the mean concentration at which three out of 12 inflammation markers are elevated in the sputum of exposed workers. However, the clinical relevance of this finding is unclear and the margin to the MAK value is considered sufficient. The effects on the lung is the most sensitive endpoint, so vapours and aerosols of bitumen are assigned to Peak Limitation Category II with an excursion factor of 2. All in all, the investigated straight‐run and air‐rectified bitumens did not exhibit distinct genotoxic or carcinogenic properties. However, due to the wide range in the chemical composition, harmful emissions of carcinogenic and mutagenic substances during high‐temperature processing cannot be completely excluded. Therefore, vapours and aerosols of straight‐run and air‐rectified bitumens, as commonly used in road paving, are regarded as suspicious carcinogens and classified in Carcinogen Category 3 B. As no data are available for developmental toxicity they are assigned to Pregnancy Risk Group D. Skin contact may contribute significantly to systemic toxicity and the "H" notation is confirmed. Sensitization is not expected from the available data. Oxidized Bitumen There are no inhalation studies available for evaluation of the carcinogenicity of oxidized bitumen ("Roofing Bitumen"). The new animal studies published since 2001 and most of the previous studies show the carcinogenicity of condensates of vapours and aerosols of oxidized bitumens in skin painting studies in mice, so that a significant number of tested oxidized bitumens must be considered carcinogenic. The positive animal experiments on the carcinogenicity are consistent with the results of a genotoxicity study in roofing workers with increased DNA strand break rates. Vapours and aerosols of oxidized bitumen are classified in Carcinogen Category 2. A MAK value could not be derived. Mutations in bacteria and higher levels of benzo[a]pyrene in oxidized bitumen condensates compared to those of straight‐run and air‐rectified bitumen and the systemic availability of inhaled vapours and aerosols of oxidized bitumen support suspicion of germ cell mutagenicity. Therefore, vapours and aerosols of oxidized bitumen are classified in Category 3 B for germ cell mutagens. Skin contact may contribute significantly to systemic toxicity and the "H" notation is confirmed. Sensitization is not expected from the available data.